ESTIMATION OF MARKET RISK IN UKRAINE USING VAR METHODOLOGY - Trofymchuk, O. M.; Kozhukhivska, O. A.; Bidyuk, P. I.; Kozhukhivskyi, A. D. (Radio Electronics, Computer Science, Control, 2013)
The emergence of a market risk due to performing operations with currency can result in substantial financial losses. That is why such situations require carrying out of profound analysis and management of respective risks. The market risk of this kind is characterized with possible losses of financial resources due to incorrectly performed operations with currency. The paper considers the possibility of application of the VaR methodology to the bank currency portfolio using the following methods: delta-normal, as well as the methods of historical modeling and Monte-Carlo simulation. While performing the computing experiments actual data used from the currency market of Ukraine. Quite acceptable results of forecasting possible losses were received by making use of Monte-Carlo simulation that hypothetically can take into account possible variations of the market exchange rates. It was established that the risk forecasting errors appear only due to non-predictable abrupt changes of exchange rates.